2022
DOI: 10.3389/fpos.2022.849763
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Induced Misinformation on YouTube: An Analysis of User Commentary

Abstract: Several scholars have demonstrated a positive link between political polarization and the resistance to COVID-19 prevention measures. At the same time, political polarization has also been associated with the spread of misinformation. This study investigates the theoretical linkages between polarization and misinformation and measures the flow of misinformation about COVID-19 in the comment sections of four popular YouTube channels for over 16 months using big data sources and methods. For the analysis, we dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…7 Suter, et al found that up to 25% of comments on YouTube videos contained misinformation, and that, perhaps unsurprisingly, 'fake comments receive more attention and attract more fake replies than factual comments'. 8 Instagram, owned by Facebook, adheres to the latter's strategies for 'reducing the spread of misinformation', 9 but do not appear to be trying to actively completely prevent it.…”
mentioning
confidence: 99%
“…7 Suter, et al found that up to 25% of comments on YouTube videos contained misinformation, and that, perhaps unsurprisingly, 'fake comments receive more attention and attract more fake replies than factual comments'. 8 Instagram, owned by Facebook, adheres to the latter's strategies for 'reducing the spread of misinformation', 9 but do not appear to be trying to actively completely prevent it.…”
mentioning
confidence: 99%